Surgical site infection; effect of contamination and duration of surgical procedure - Muhammad Iqbal, Muhammad Naeem Zia, Sadaf Ijaz, Naveed Akhtar Malik (Journal of Rawalpindi Medical College, 2022)
Introduction: Surgical site infections are responsible for increased treatment cost, prolonged hospital stay and increased morbidity on surgical floor. Increased level of per operative contamination and prolonged surgery increases the incidence of surgical site infections. Objective: To know the effect of contamination and duration of surgery on the incidence of surgical site infections in emergency surgical patients so that specific strategies can be developed to decrease the morbidity and mortality caused by these infections. Materials and Methods: All the patients who underwent general surgical operations on an emergency basis at the surgical unit-1 of the Benazir Bhutto Hospital Rawalpindi from 01-01-2019 to 31-12-2020 were evaluated for surgical site infections. The level of contamination per operatively and duration of surgery were documented. Surgical site infections suspected clinically were confirmed by culture and sensitivity. Results: Among 2202 emergency-operated patients, two hundred and thirty-seven patients (10.76%) had surgical site infection confirmed on culture and sensitivity (C/S) report. About sixty-five percent of patients were male. Of two hundred and thirty-seven positive patients, seventy (29.09%) patients underwent laparotomy for penetrating and blunt abdominal trauma. About fifty-eight percent of SSI patients had contaminated wounds per operatively. Operative time was one to three hours in about sixty-seven percent of SSI-positive patients. Staph aureus was present in one hundred and forty-five (79.67%) patients. E.coli was the most commonest Gram-ve micro-organism (70.95%). Conclusion: Surgical site infection causes a significant rise in morbidity on the surgical floor. Increased levels of contamination per operatively and prolonged operative time increase the incidence of SSI in emergency surgical operations.